Mobilization and Activation of the Innate Immune Response to Dengue Virus - King, Christine A.; Wegman, Adam D.; Endy, Timothy P. (Frontiers in Cellular and Infection Microbiology, 2020)
Dengue virus is an important human pathogen, infecting an estimated 400 million individuals per year and causing symptomatic disease in a subset of approximately 100 million. Much of the efforts to date describing the host response to dengue have focused on the adaptive immune response, in part because of the well-established role of antibody-dependent enhancement and T cell original sin as drivers of severe dengue upon heterotypic secondary infection. However, the innate immune system is a crucial factor in the host response to dengue, as it both governs the fate and vigor of the adaptive immune response, and mediates the acute inflammatory response in tissues. In this review, we discuss the innate inflammatory response to dengue infection focusing on the role of evolutionarily conserved innate immune cells, their effector functions, and clinical course.